2018
DOI: 10.15408/ijee.v5i1.8460
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Language Learning Strategies Used by English Students

Abstract: This research investigates the language learning strategies used by English students of Faculty of Teacher Training and Education (FKIP, hereafter) of Universitas Jambi. This research employed the Strategy Inventory for Language Learning (SILL) questionaires designed by Oxford (1990) to obtain data from 85 students of the fifth semester class 2015 studying at the English Department. The statistical analysis of the data revealed that students opted for metacognitive (Part D), social (Part F), cognitive (Part B)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The last article, Wulandari (2018) in the previous article, uses Oxford's Strategy Inventory for Language Learning (SILL) surveys to research the language learning techniques adopted by English students. The statistical analysis of the data from this quantitative study showed that students chose meta-cognitive, social, cognitive, compensatory, memory, and emotional methods, in that order, as their most often utilized language learning techniques.…”
Section: Resultsmentioning
confidence: 99%
“…The last article, Wulandari (2018) in the previous article, uses Oxford's Strategy Inventory for Language Learning (SILL) surveys to research the language learning techniques adopted by English students. The statistical analysis of the data from this quantitative study showed that students chose meta-cognitive, social, cognitive, compensatory, memory, and emotional methods, in that order, as their most often utilized language learning techniques.…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore to very paramount to evaluate the English and foreign language as part of the curriculum in Indonesia (Mappiasse & Bin Sihes, 2014). Wulandari (2018) said that said on the result of evaluation research teachers prepared to conduct variety of teaching strategies in their classrooms. Evaluation on English course program has become a focus of researchers on the aspect of teaching materials and the result of evaluation research impact to learners' language development (Bandu et al, 2021;Kanina, 2016;Purwanti, 2019;Solhi et al, 2020).…”
Section: A Introductionmentioning
confidence: 99%
“…On the other hand, this research result didn't differentiate the participants in high or low students in performing speaking ability. Wulandari (2018) evaluated language learning strategies used by English students. Her study mentioned that six language strategies were revealed, and the most used were effective.…”
Section: Introductionmentioning
confidence: 99%